The competencies of registered nurses working in care homes: a modified Delphi study - Stanyon, Miriam; Goldberg, Sarah E.; Astle, Anita; Griffiths, Amanda; Gordon, Adam L. (Oxford University Press, 2017)
BACKGROUND: Registered Nurses (RNs) working in UK care homes receive most of their training in acute hospitals. At present the role of care home nursing is underdeveloped and it is seen as a low status career. We describe here research to define core competencies for RNs working in UK care homes.